2019
DOI: 10.1007/s10616-019-00300-x
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates affect the in vitro expansion of human hematopoietic stem cell

Abstract: Phthalates are esters of phthalic acid used industrially as plastic additives, however, these are not covalently bound to the polymer matrix and therefore can be released to the environment. The aim of this study was to evaluate the effect of four phthalates: dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), diethyl phthalate (DEP) and diethylhexyl phthalate (DEHP) on the in vitro expansion of human hematopoietic cells from umbilical cord blood. For this, 0.5 9 10 6 cells/mL were exposure to concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…MEHP in a high concentration (1,000 µmol/L or 164,110 ng/mL) decreased the expression of genes related to mesoderm and the primary germ cells, induced cytotoxicity, and reduced cell proliferation and viability (Shi et al, 2013). Studies examining the effects on in vitro expansion of human hematopoietic cells from umbilical cord blood found that four phthalates-DBP, benzyl butyl phthalate (BBP), DEP, and DEHP decreased the cell expansion with DBP being the most cytotoxic (Gutierrez-Garcia et al, 2019).…”
Section: Effect Of Phthalates On Different Tissues Embryonic Stem Celmentioning
confidence: 99%
See 2 more Smart Citations
“…MEHP in a high concentration (1,000 µmol/L or 164,110 ng/mL) decreased the expression of genes related to mesoderm and the primary germ cells, induced cytotoxicity, and reduced cell proliferation and viability (Shi et al, 2013). Studies examining the effects on in vitro expansion of human hematopoietic cells from umbilical cord blood found that four phthalates-DBP, benzyl butyl phthalate (BBP), DEP, and DEHP decreased the cell expansion with DBP being the most cytotoxic (Gutierrez-Garcia et al, 2019).…”
Section: Effect Of Phthalates On Different Tissues Embryonic Stem Celmentioning
confidence: 99%
“…Phthalates can act as endocrine disrupting chemicals (EDCs) by exerting strong antiandrogenic (Doyle et al, 2013;Martino-Andrade et al, 2016) and weak estrogenic (Lee et al, 2012;Huang P. C. et al, 2014) effects. Though, EDC exposure can be harmful at any stage of human life, the developing human fetus in a phase of rapid proliferative growth in utero may be particularly vulnerable (Gutierrez-Garcia et al, 2019). The in utero environment or the preconception time period has been regarded as the most vulnerable period of growth and development to environmental insults (Chapin et al, 2004).…”
Section: Effect Of Phthalates As Endocrine Disrupting Chemicals On Emmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further investigations are required to determine if DEHP exposure in uences other physiological processes. According to a recent study, DEHP affects the function of human haematopoietic stem and progenitor cells (HSPCs) isolated from human umbilical cord blood [5]. DEHP also impairs the migration and colony-forming capacity of human CD34 + HSPCs [6].…”
Section: Introductionmentioning
confidence: 99%
“…We focus on the effects of environmental stressors that impact these operations. We also examine cell viability to analyze toxicity and provide a fuller picture of a toxicant’s effect, by correlating cell number to cell behavior[6,7].…”
Section: Introductionmentioning
confidence: 99%